2005
DOI: 10.1016/j.nuclphysa.2005.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Is nuclear matter perturbative with low-momentum interactions?

Abstract: The nonperturbative nature of inter-nucleon interactions is explored by varying the momentum cutoff of a two-nucleon potential. Conventional force models, which have large cutoffs, are nonperturbative because of strong short-range repulsion, the iterated tensor interaction, and the presence of bound or nearly-bound states. But for low-momentum interactions with cutoffs around 2 fm −1 , the softened potential combined with Pauli blocking leads to corrections in nuclear matter in the particleparticle channel tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
502
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(530 citation statements)
references
References 46 publications
28
502
0
Order By: Relevance
“…The applicability of a perturbative expansion scheme for nuclear matter with low-momentum interactions, which is the basic hypothesis behind our approach, is discussed in Ref. [75]. Further studies towards foundations along these lines are presently being pursued.…”
Section: Summary Conclusion and Further Commentsmentioning
confidence: 99%
“…The applicability of a perturbative expansion scheme for nuclear matter with low-momentum interactions, which is the basic hypothesis behind our approach, is discussed in Ref. [75]. Further studies towards foundations along these lines are presently being pursued.…”
Section: Summary Conclusion and Further Commentsmentioning
confidence: 99%
“…Microscopic calculations start from NN and three-nucleon interactions that reproduce NN scattering and selected few-nucleon data. In addition to the conventional variational [13,14] and Brueckner [15,16] calculations, renormalization-group methods coupled with effective field theory provide new insights to nuclear forces and the possibility of a perturbative and thus systematic approach to nuclear matter with theoretical error estimates [17,18]. However, all wave functions that are typically used only include two-nucleon correlations and omit four-nucleon correlations that could be important to describe alpha particle formation at low densities.…”
Section: Introductionmentioning
confidence: 99%
“…However, as it was shown in Refs. [22][23][24], in the case of soft N N interactions, a perturbative approach can be successfully used for nuclear matter calculations. In particular, the authors of Refs.…”
mentioning
confidence: 99%
“…In particular, the authors of Refs. [22,23] demonstrated that the dominant particle-particle channel contributions become perturbative in nuclear matter calculations using so-called low-momentum N N interactions (V low−k ) obtained by renormalization group methods [25,26] from Argonne AV 18 and chiral effective field theory N 3 LO N N interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation